Analisis Risiko Produksi Jeruk Lemon Varietas California dengan Metode Z-Score dan Value at Risk - Didik, Editya Nugraha; Saidah, Zumi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
CV. Berkah Tani is widely recognized as a reputable producer of lemon with a strong record of consumer loyalty. However, the company has faced various production challenges, including fluctuating yields and instances of crop failure. These conditions indicate the presence of risks in the cultivation process. This study aims to identify the sources of these risks, assess their probabilities and impacts, and formulate appropriate management strategies to help the farm achieve its production and profit targets. The research adopts a case study method with a qualitative approach, employing Z-Score and Value at Risk (VaR) analyses. The results reveal three main risk sources affecting CV. Berkah Tani's farming activities: Pests and Diseases with a probability of 33.50% and an estimated loss of Rp 20,522,514; Climate and Weather with a probability of 23.92% and an estimated loss of Rp 18,918,012; and Labor with a probability of 19.04% and an estimated loss of Rp 17,560,171. Based on risk measurement and risk mapping analysis, both preventive and mitigation strategies were developed to minimize the impact of these risks. Among the three, Pests and Diseases were identified as the most critical risk factor. Suggested strategies to mitigate this risk include the use of yellow traps to manage fruit fly infestations, rotating chemical and botanical pesticides to control pest resistance, and conducting regular monitoring and early identification of symptoms of pest and disease attacks on lemon plants.